2009
DOI: 10.1097/gme.0b013e31819d4113
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus and other cardiovascular risk factors are no more common during menopause

Abstract: Menopause is a biological condition of the human species, for which has recently received attempts at medicalization that were not always justified. If menopause is not accompanied by any other cardiovascular risk factor independently of age, the stigma of menopause being considered a risk factor should cease. Although the results have the strength of a prospective study, the sample size forced us to consider these findings as preliminary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
2
24
5
Order By: Relevance
“…The contradictory study results might be attributed to the causes of menopause. The current study focused on natural menopause, and the results are consistent with most of the previous studies which rejected an increased risk for hypertension or DM with menopause 8,9,29,30,33) . Body weight, smoking, alcohol consumption, and physical activity are now well-known influential factors on blood pressure and glucose metabolism.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The contradictory study results might be attributed to the causes of menopause. The current study focused on natural menopause, and the results are consistent with most of the previous studies which rejected an increased risk for hypertension or DM with menopause 8,9,29,30,33) . Body weight, smoking, alcohol consumption, and physical activity are now well-known influential factors on blood pressure and glucose metabolism.…”
Section: Discussionsupporting
confidence: 78%
“…Associations between menopause or AAM and CRF could be largely confounded by chronological age [8][9][10][11] and daily lifestyle, such as body weight, smoking, alcohol consumption, or physical activity [10][11][12] . Chronological age and lifestyle are recognized as influential factors on CRF 1,13) and are mutually correlated 14,15) .…”
Section: Natural Menopause Status and Age At Menopausementioning
confidence: 99%
“…A study involving 475 women followed up for 6 years found no changes in lipid profile during the passage from premenopause to postmenopause, independent of age and physical activity. 22 Another longitudinal study with 4 years of follow-up indicated that after controlling for age and body mass index, only increased levels of TC could be explained by menopause. 23 Our results differ from those of some previous cross-sectional or casecontrol studies.…”
Section: Discussionmentioning
confidence: 98%
“…While risk of cardiovascular disease increases for women after menopause, there is no evidence for an increase in mean blood pressure (BP) due to the menopausal transition when results account for general age-related increases in BP (1, 2). However, in a study of hypertensive women, Routledge et al (3) noted that post-menopausal status was a significant predictor of which women had a nighttime decline in BP of less than 10% of waking values (“non-dippers”).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, this study was initiated with simultaneous objective ambulatory monitoring of BP and HFs, the latter through use of a skin conductance monitor, as well as questionnaire and diary assessments of HFs. This enables observation of (1) the association of HFs, measured subjectively through questionnaires and diaries and objectively through skin conductance, with mean BP, and (2) the association of subjective and objective HFs with transient variation in BP. Diary, laboratory and ambulatory studies have noted significantly fewer HFs during sleep than at other times of day, possibly due to lowered internal temperature (1115).…”
Section: Introductionmentioning
confidence: 99%